Evaluation of stimulated reservoir volume in laboratory hydraulic fracturing with oil, water and liquid carbon dioxide under microscopy using the fluorescence method - Bennour, Ziad; Watanabe, S.; Chen, Y.; Ishida, T.; Akai, T. (SPRINGER HEIDELBERG, 2018)
© 2017, Springer International Publishing AG. In shale gas industry, it is desired to develop new reservoir fracturing and enhanced gas recovery technologies to replace the conventional hydraulic fracturing (HF), in order to reduce water usage to guarantee the environmental sustainability and boost individual well production. As the goal of HF is to create high conductivity fracturing networks as flow paths for gas, it is necessary for HF to activate and connect existing natural fractures to generate large fractures network. The success or failure of HF often depends on the stimulated reservoir volume (SRV) which is characterized by the quantity and the quality of the fractures network resulted. This study investigates the micro-fractures network resulted in laboratory HF experiments in 2-D thin polished section by using a fluorescent method supported by advanced computerized image analysis. To evaluate difference of resulted SRV due to the difference of fracturing fluid, using three cylindrical shale cores and three granite cubes having fractures induced by HF using three fluids having different viscosity; oil, water and liquid carbon dioxide (L-CO2). The observation and statistical analysis of fractures induced in HF by the three different fluid viscosities using the fluorescent method showed ability of L-CO2 injection to achieve effective stimulation. The results suggest that employing a low viscosity fluid in HF of shale reservoirs can achieve more productive network with better SRV. In addition, the observation seems to be consistent with the tendency observed in the previous researches.